Combined Medial Plate and Intramedullary Nailing for the Fixation of Extra-Articular Proximal Tibial Fractures: a Biomechanics Study - Lu, Yao; Zhao, Jiasong; Huang, Qiang; Ren, Cheng; Sun, Liang; Wang, Qian; Li, Ming; Zhang, Congming; Xue, Hanzhong; Li, Zhong; Zhang, Kun; Xu, Yibo; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: The extra-articular proximal tibial fractures continue to have high malunion rates despite development in intramedullary nailing (IMN) technology. Combined plate and IMN fixation can increase mechanical stability. The purpose of this study was to investigate combined plate and IMN for the treatment of extra-articular distal tibial fracture using a biomechanical model. Methods: A 10-mm defective osteotomy was created in the fourth-generation composite tibia to simulate extra-articular proximal tibial fractures(AO/OTA 41A2). The fractures were stabilized with IMN alone (IMN group), IMN with supplementary medial plate (M-IMN group), and IMN with supplementary lateral plate (L-IMN group). The biomechanical properties of each specimen were tested under axial compression loading, bending stress, and cyclic loading. The maximum displacement of the fragments and implant-bone construct failure was recorded. Results: The maximum displacement of the M-IMN group was significantly less than either the L-IMN or IMN group in both axial compression loading and bending stress (p < 0.05 for both comparisons). All specimens in the three groups survived in 10000 cyclic loading without hardware deformation. The maximum stiffness of failure was similar between the M-IMN and L-IMN groups, but the IMN group was statistically lower than either the L-IMN or the IMN group (P < 0.05). Conclusions: The results indicated that combined medial plate and IMN fixation could effectively increase the mechanical stability of proximal tibial fractures.